Temperature and time effect of thermal aging treatment on microstructure and corrosion resistance of UNS S31803 duplex stainless steel (Research, Society and Development, 2021)
Duplex stainless steels correspond to a class of steel in which the microstructure is composed basically by the phases ferrite and austenite. Given the metastable character of ferrite, associated phase transformations can occur during thermal treatments, which can lead to a reduction in corrosion resistance. Therefore, the aim of this work was to evaluate the influence of the solution-treated at 1100°C for 30min and aging at 500 and 600°C for 1, 3 and 12h, on the microstructure and corrosion resistance of DSS UNS S31803. The steels were characterized by SEM, EDS, XRD, hardness, microhardness and thermal analysis. The steels aged at 500°C for 1h presented the phase alpha line dispersed in the ferrite, and the steels aged at 600°C for 12h presented the phases alpha line, sigma and chi. In the assays of double cycle potentiodynamic reactivation in solution of 0.5M H2SO4 and 0.01M KSNC, it was observed that no sensitization occurred. Furthermore, in the tests of cyclic potentiodynamic polarization, in 3.5% NaCl solution, it was verified that the precipitation of the alpha line phase did not alter corrosion resistance; nevertheless, the sigma phase reduced corrosion resistance.